2021
DOI: 10.3390/jcm10040710
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Biologics and Postoperative Surgical Morbidity in Ulcerative Colitis: A Review

Abstract: Background: With the paradigm shift related to the overspread use of biological agents in the treatment of inflammatory bowel diseases (IBD), several questions emerged from the surgical perspective. Whether the use of biologicals would be associated with higher rates of postoperative complications in ulcerative colitis (UC) patients still remains controversial. Aims: We aimed to analyze the literature, searching for studies that correlated postoperative complications and preoperative exposure to biologics in U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The data regarding the association between steroid use and complications after IPAA have been conflicting [ [16] , [17] , [18] ]. While initial reports from the beginning of the biologic era reported a higher incidence of postoperative complications, subsequent reports did not confirm these findings [ 19 , 20 ]. In our study, we identified steroid use as being associated with postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The data regarding the association between steroid use and complications after IPAA have been conflicting [ [16] , [17] , [18] ]. While initial reports from the beginning of the biologic era reported a higher incidence of postoperative complications, subsequent reports did not confirm these findings [ 19 , 20 ]. In our study, we identified steroid use as being associated with postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The length of the disease course can affect the postoperative outcome. Patients with a disease course are usually more severely ill than those with a milder disease course, which makes them more susceptible to infection, resulting in a worse prognosis [48]. The effects of other infectious factors, such as ischemia along the suture line, large wound area, and insufficient collagen synthesis in IBD patients are also not negligible [32].…”
Section: Discussionmentioning
confidence: 99%
“…The data on TNFα antibodies are less consistent but the overall risk appears to be increased. There are only sparse data about the preoperative use of vedolizumab and ustekinumab [122]. Therefore, for ongoing anti-TNF-α therapy or a current steroid dose of more than 20 mg per day, a three-step approach is advisable to reduce the risk for complications.…”
Section: What To Tell Patients With Regard To Covid19 and Vaccination...mentioning
confidence: 99%